Sociolinguistics and Language Education in Nigeria - Iwuchukwu, Godwin C. S.; Iwuchukwu, Rita Ngozi (Global Journal of Social Sciences Studies, 2018)
This paper sets out to investigate sociolinguistics and language education in Nigeria. It aims at unveiling the social factors that influence language as well as the interaction of language with the social structures with the view of determining its place in the language teaching and learning. The work analyses the unstable education policies in Nigeria and their language components with practical realities of teaching Languages in government public schools especially, the Federal Government College. The choice of Federal Government Girls’ College, Calabar is predicated on the fact that it is among the public schools in Nigeria that receives reasonable funding, being owned by the Federal government. Also, it presents a good sociolinguistic environment with several students from different multicultural and multilinguistic backgrounds. English language is one of the compulsory subjects which every student must offer. In addition to English, one Nigerian Language is offered. Thus, there are teachers of English and Nigerian Languages who teach the students and majority possess one native language or the other. The quantitative research technique, including participant observation and survey was used which captured the teachers of the languages and the challenges encountered in the process of teaching in the different classes. Furthermore, the students were asked questions on the performance of the teachers in various classroom situations. The result of our findings reveals that most of the language teachers lack adequate knowledge of sociolinguistics which complicates their ability to maturely handle the classroom situations though they are certified professional teachers.